Sierra Leone. - African Dept., International Monetary Fund (IMF Staff Country Reports., 2013)
KEY ISSUESContext. Against the background of challenging economic and social conditions, Sierra Leone has been making progress since the end of the civil conflict in 2002. Theeconomy has been growing at a solid pace, inflation has been trending down, and sociopoliticalstability is taking hold. Going forward, the authorities need to strengthen policyimplementation particularly in the fiscal area to entrench macroeconomic stability, supportprivate sector development and job creation, and develop social policies to protect themost vulnerable groups in the population. Consultation focus. Policy disc.